Lithium supplement additive and preparation method thereof, positive electrode sheet and secondary battery

By using a combination of lithium-rich materials and composite catalytic materials in lithium-ion secondary batteries, combining conductive materials and fibers, the problems of irreversible capacity loss and poor conductivity of lithium-ion secondary batteries are solved, and the battery performance and battery life are improved extend.

CN117525422BActive Publication Date: 2024-12-20SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311665396.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2024-12-20
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

The lithium-ion secondary battery produces a solid electrolyte interface mask during the first charging and discharging process, resulting in irreversible capacity loss and reducing the efficiency and cycle life of Coulomb. The existing lithium supplement additive has high lithium potential and poor conductivity, which limits the improvement of battery performance.

Method used

The composite catalytic material is adopted to combine lithium-rich materials and composite catalytic materials, which include metal compound catalysts and metal catalysts supported thereon. The composite catalytic material formed has good catalytic and conductive properties, reduces the deliquification potential of lithium-rich materials, and improves the Specific capacity and enhance conductivity and stability through the distribution of conductive materials and fibers.

Benefits of technology

It effectively reduces the deliquification potential of lithium-rich materials, improves the specific capacity and conductivity of lithium-enhancing additives, extends the cycle life of the battery and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117525422B_ABST
    Figure CN117525422B_ABST
Patent Text Reader

Abstract

The present application provides a lithium supplement additive and a preparation method thereof, a positive electrode plate and a secondary battery. The lithium supplement additive includes a lithium-rich material and a composite catalytic material. The composite catalytic material is distributed on the outer layer of the lithium-rich material, and the composite catalytic material includes a metal compound catalyst and a metal catalyst supported on the metal compound catalyst. In the embodiment of the present application, both the metal compound catalyst and the metal catalyst have catalytic properties. And the metal catalyst has good electrical conductivity, which is beneficial to enhance the catalytic effect of the composite catalytic material. The composite catalytic material formed by the metal catalyst and the metal compound catalyst has good catalytic performance and electrical conductivity, which can better promote the lithium-rich material to fully delithiate at a lower potential, thereby increasing the specific capacity of the lithium supplement additive. In addition, the metal catalyst is supported on the metal compound catalyst, and the binding force between the metal catalyst and the metal compound catalyst is strong, which reduces the loss of the metal catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium supplement additive and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] During the first charge and discharge process of a battery such as a lithium-ion secondary battery, a large amount of solid electrolyte interface film (SEI film) will be produced on the surface of the negative electrode of the battery, which consumes the limited lithium ions and electrolyte in the battery, causing irreversible capacity loss, resulting in a decrease in the coulombic efficiency of the lithium-ion secondary battery, and directly affecting the cycle life and energy density of the lithium-ion secondary battery. At present, the loss of this part of irreversible capacity can be eliminated by replenishing lithium at the positive electrode, thereby improving the energy density and other electrical properties of the battery. However, the lithium release potential of the existing lithium-replenishing additives is relatively high, even exceeding the commonly used operating voltage range of the existing battery system, which increases the difficulty of applying the lithium-replenishing additives. In addition, the existing lithium-replenishing additives themselves have a low electrical conductivity, which seriously affects the release of lithium ions and limits the improvement of the performance of lithium-ion secondary batteries. Summary of the invention

[0003] The present application provides a lithium supplement additive and a preparation method thereof, a positive electrode plate and a secondary battery.

[0004] In a first aspect, the present application provides a lithium supplement additive, the lithium supplement additive comprising a lithium-rich material and a composite catalytic material. The composite catalytic material is distributed on the outer layer of the lithium-rich material, and the composite catalytic material comprises a metal compound catalyst and a metal catalyst supported on the metal compound catalyst.

[0005] In the embodiments of the present application, on the one hand, the metal compound catalyst has good catalytic performance and can effectively reduce the lithium decomposition potential of the lithium-rich material. The metal catalyst has a certain catalytic effect and better conductivity. The electronic conductive environment formed by the metal catalyst is more conducive to enhancing the catalytic effect of the composite catalytic material. The composite catalytic material formed by the metal catalyst and the metal compound catalyst not only has good catalytic performance, but also has good electrical conductivity, which can better promote the lithium-rich material to fully delithium at a lower potential, thereby improving the specific capacity of the lithium supplement additive. On the other hand, the metal catalyst is loaded on the metal compound catalyst, and the bonding force between the metal catalyst and the metal compound catalyst is strong, so that the metal catalyst is not easy to fall off, reducing the loss of the metal catalyst, thereby ensuring that the composite catalytic material has good electrical conductivity.

[0006] In one embodiment, the metal compound catalyst is a one-dimensional structure; and / or, the metal catalyst is a metal particle or a metal atom cluster.

[0007] In one embodiment, the metal catalyst is at least partially embedded in the one-dimensional structured metal compound catalyst.

[0008] In one embodiment, the lithium-rich material forms a core, and the composite catalytic material is coated on an outer layer of the core.

[0009] In one embodiment, the lithium supplement additive further includes a conductive material, the composite catalytic material is entangled and distributed on the outer surface of the inner core, and the conductive material is filled in the gaps between the metal compound catalysts of the one-dimensional structure.

[0010] In one embodiment, the conductive material is coated on the outer surface of the inner core, and the composite catalytic material is wrapped around the outer surface of the conductive material.

[0011] In one embodiment, the composite catalytic material is wrapped around the outer surface of the inner core, and the conductive material is wrapped around the outer surface of the composite catalytic material.

[0012] In one embodiment, the lithium supplement additive also includes conductive fibers, the composite catalytic material is coated on the outer surface of the inner core, and the conductive fibers are wrapped around the outer surface of the composite catalytic material; or the conductive fibers are wrapped around the outer surface of the inner core, and the composite catalytic material is wrapped around the outer surface of the conductive fibers.

[0013] In one embodiment, the lithium supplement additive includes conductive fibers, and the conductive fibers are wound around the outer periphery of the one-dimensional structured metal compound catalyst.

[0014] In one embodiment, the inner core is a secondary particle, the secondary particle is composed of a plurality of primary particles, part of the composite catalytic material is filled in the gaps between the primary particles; and / or part of the composite catalytic material is coated on the outer surface of the primary particles.

[0015] In one embodiment, the metal compound catalyst includes one or more of transition metal carbides, transition metal nitrides, transition metal borides, and transition metal sulfides.

[0016] In one embodiment, the metal catalyst includes one or more of nickel, iron, cobalt, manganese, copper, zinc, titanium, and chromium.

[0017] In one embodiment, the mass ratio of the lithium-rich material, the metal compound catalyst and the metal catalyst is 100:(8-36):(4-22).

[0018] In one embodiment, the one-dimensional structured metal compound catalyst has a length ranging from 3 μm to 20 μm and a diameter ranging from 200 nm to 800 nm.

[0019] In a second aspect, the present application provides a method for preparing a lithium supplement additive, the method for preparing the lithium supplement additive comprising:

[0020] The composite catalytic material is mixed with the lithium-rich material, and heated or freeze-dried to obtain the lithium supplement additive.

[0021] In a third aspect, the present application provides a positive electrode plate, wherein the positive electrode plate includes the lithium supplement additive as described above, or includes the lithium supplement additive prepared by the preparation method of the lithium supplement additive as described above.

[0022] In a fourth aspect, the present application provides a secondary battery, comprising a negative electrode plate, a separator, and the positive electrode plate as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments of the present application will be described below.

[0024] Figure 1 Schematic diagram (1) of a lithium supplement additive provided in one embodiment of the present application.

[0025] Figure 2 It is a schematic diagram of a composite catalytic material and conductive fiber provided in one embodiment of the present application.

[0026] Figure 3 Schematic diagram (2) of a lithium supplement additive provided in one embodiment of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0028] In this document, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0029] In addition, in this article, directional terms such as "upper" and "lower" are defined relative to the orientation of the structure schematically placed in the drawings. It should be understood that these directional terms are relative concepts. They are used for relative description and clarification, and they can change accordingly according to the change of the orientation of the structure.

[0030] For ease of understanding, the English abbreviations and related technical terms involved in the embodiments of the present application are explained and described below.

[0031] During the first charge and discharge process of a battery such as a lithium-ion secondary battery, a large amount of solid electrolyte interface film (SEI film) will be produced on the surface of the negative electrode of the battery, which consumes the limited lithium ions and electrolyte in the battery, greatly reducing the capacity of lithium ions and causing irreversible capacity loss. During the first discharge, the lithium ions extracted from the negative electrode are much smaller than the lithium ions extracted from the positive electrode during charging, resulting in a decrease in the coulombic efficiency of the lithium-ion secondary battery, which directly affects the cycle life and energy density of the lithium-ion secondary battery. To address this problem, this part of the irreversible capacity loss can usually be eliminated by replenishing lithium at the positive electrode, thereby improving the battery energy density and other electrical properties. However, existing lithium-rich materials have the problems of poor conductivity and high lithium release potential, which are not conducive to the promotion and application of lithium-rich materials and limit the improvement of the performance of lithium-ion secondary batteries.

[0032] The present application provides a lithium supplement additive 1, which is applied to the positive electrode of the battery to pre-lithiate the positive electrode, and to add lithium to the battery to supplement lithium ions before the battery is operated. The lithium supplement additive 1 provided by the present application has high conductivity and low lithium release potential, and is applied to lithium ion secondary batteries to effectively improve the performance of lithium ion secondary batteries.

[0033] In one embodiment, when the lithium supplement additive 1 is used, the lithium supplement additive 1 can be applied to the outer surface of the battery positive electrode plate, or the lithium supplement additive 1 can be embedded in the outer surface of the battery positive electrode plate. In other embodiments, the lithium supplement additive 1 can also be added during the preparation of the battery positive electrode slurry, so that the lithium supplement additive 1 is dispersed on the outer surface and inside of the battery positive electrode plate.

[0034] See also Figure 1 The present application provides a lithium supplement additive 1, which includes a lithium-rich material 10 and a composite catalytic material 20. The composite catalytic material 20 is distributed on the outer layer of the lithium-rich material 10. The composite catalytic material 20 includes a metal compound catalyst 21 and a metal catalyst 22 loaded on the metal compound catalyst 21.

[0035] The lithium supplement additive 1 includes a plurality of particles. Figure 1 The above is a schematic diagram of one particle of the lithium supplement additive 1. In one embodiment, the lithium supplement additive 1 is spherical or approximately spherical.

[0036] The lithium supplement additive 1 includes a lithium-rich material 10, which is used to supplement lithium. During the first charging process, lithium (Li) in the lithium-rich material 10 can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, thereby increasing the total capacity and energy density of the battery.

[0037] The composite catalytic material 20 in the lithium supplement additive 1 is located on the outer surface of the lithium-rich material 10 . The composite catalytic material 20 may be directly distributed on the outer surface of the lithium-rich material 10 or indirectly distributed on the outer surface of the lithium-rich material 10 .

[0038] The composite catalytic material 20 includes a metal compound catalyst 21 and a metal catalyst 22, and both the metal compound catalyst 21 and the metal catalyst 22 have the ability to catalyze the decomposition of the lithium-rich material 10. The metal compound catalyst 21 and the metal catalyst 22 can effectively reduce the decomposition potential of the lithium-rich material 10. For example, if the lithium-rich material 10 is selected from lithium-rich compounds with higher delithiation voltages, these lithium-rich compounds require a higher charging voltage for delithiation, and there is a technical problem of high platform voltage. Even the high voltage exceeds the commonly used operating voltage range of existing battery systems, which increases the difficulty of applying the lithium-rich material 10. In addition, when the lithium-ion battery is charged and discharged for the first time, the higher voltage will also make the lithium-rich compound and the positive electrode material easily generate oxygen, and the generated oxygen is further oxidized to cause oxidative decomposition of the electrolyte, thereby resulting in reduced safety and performance of the lithium-ion battery.

[0039] In the embodiment of the present application, after the composite catalytic material 20 is added to the lithium-rich material 10, the lithium-rich material 10 can be fully delithiated at a lower potential under the action of the composite catalytic material 20, thereby improving the specific capacity of the lithium supplement additive 1.

[0040] In the composite catalytic material 20, compared with the metal catalyst 22, the metal compound catalyst 21 has good catalytic performance, and can effectively reduce the delithiation potential of the lithium-rich material 10. Compared with the metal compound catalyst 21, the metal catalyst 22 has a certain catalytic effect and better conductivity. The electronic conductive environment formed by the metal catalyst 22 is more conducive to enhancing the catalytic effect of the composite catalytic material 20. The composite catalytic material 20 formed by the metal catalyst 22 and the metal compound catalyst 21 not only has good catalytic performance, but also has good conductivity.

[0041] In the present application, the metal catalyst 22 is loaded on the metal compound catalyst 21, and the binding force between the metal catalyst 22 and the metal compound catalyst 21 is strong, so that the metal catalyst 22 is not easy to fall off, reducing the loss of the metal catalyst 22, thereby ensuring that the composite catalytic material 20 has good conductive properties.

[0042] In general, in the embodiments of the present application, a composite of a metal catalyst 22 and a metal compound catalyst 21 is selected as the composite catalytic material 20, which can better promote the lithium-rich material 10 to fully delithiate at a lower potential, effectively reduce the lithium-decomposition potential of the lithium-rich material 10, and thus improve the specific capacity of the lithium-supplementing additive 1.

[0043] See also Figure 2 In one embodiment, the metal compound catalyst 21 is a one-dimensional structure. The metal compound catalyst 21 is a linear fiber. In the embodiment of the present application, the one-dimensional structure of the metal compound catalyst 21 has a larger specific surface area, increases the catalytic sites of the metal compound catalyst 21, improves the catalytic ability of the metal compound catalyst 21, and helps to effectively reduce the decomposition potential of the lithium-rich material 10.

[0044] In one embodiment, the metal catalyst 22 is a metal particle or a metal atom cluster. The metal catalyst 22 in the form of a metal particle or a metal atom cluster is more easily loaded on the metal compound catalyst 21, which not only simplifies the preparation process of the composite catalytic material 20, but also improves the binding force between the metal catalyst 22 and the metal compound catalyst 21.

[0045] In one embodiment, the metal catalyst 22 is at least partially embedded in the one-dimensional structure of the metal compound catalyst 21. In the embodiment of the present application, at least a portion of the metal catalyst 22 is embedded in the metal compound catalyst 21, which increases the contact area between the metal catalyst 22 and the metal compound catalyst 21, helps to improve the conductivity of the metal compound catalyst 21, thereby enhancing the catalytic effect of the metal compound catalyst 21, and helps to effectively reduce the decomposition potential of the lithium-rich material 10.

[0046] In one embodiment, part of the metal catalyst 22 is embedded in the metal compound catalyst 21 , and another part of the metal catalyst 22 is filled into the gaps between the metal compound catalysts 21 of the one-dimensional structure.

[0047] In one embodiment, the lithium-rich material 10 forms a core, and the composite catalytic material 20 is coated on the outer layer of the core. Among them, the lithium-supplementing additive 1 is a core-shell structure, the core includes the lithium-rich material 10, the outer shell is coated on the outer layer of the core, and the outer shell includes the composite catalytic material 20. In the embodiment of the present application, the shell formed by the composite catalytic material 20 can not only reduce the delithiation potential of the lithium-rich material 10, but also protect the lithium-rich material 10. The composite catalytic material 20 can prevent the external water vapor from corroding the lithium-rich material 10 and can isolate the lithium-rich material 10 from the electrolyte, reduce the occurrence of side reactions on the surface of the core, and improve the interface stability of the lithium-supplementing additive 1.

[0048] In one embodiment, the lithium supplement additive 1 includes a core and a shell, the shell is coated on the outer layer of the core, the core includes a lithium-rich material 10, the shell includes a portion of a composite catalytic material 20, and another portion of the composite catalytic material 20 is doped in the core. In the embodiment of the present application, the contact area between the composite catalytic material 20 and the lithium-rich material 10 is increased, thereby improving the catalytic effect of the composite catalytic material 20.

[0049] See also Figure 1 In one embodiment, the lithium supplement additive 1 also includes a conductive material 30, the composite catalytic material 20 is wound and distributed on the outer surface of the inner core, and the conductive material 30 is filled in the gaps between the metal compound catalysts 21 of the one-dimensional structure. Among them, the conductive material 30 can be granular or flaky. The conductive material 30 has conductivity. On the one hand, the conductive material 30 can enhance the conductivity of the lithium-rich material 10 and accelerate the transfer of electrons, reduce the polarization rate of the lithium-rich material 10, and is beneficial to improving the rate performance and cycle performance of the lithium supplement additive 1. At the same time, the electronic conductive environment formed by the conductive material 30 is more conducive to improving the conductivity of the lithium-rich material 10 and is beneficial to the delithiation of the lithium-rich material 10. On the other hand, the conductive material 30 can also be used to improve the conductivity of the composite catalytic material 20, thereby enhancing the catalytic effect of the composite catalytic material 20.

[0050] There are multiple gaps between the one-dimensional metal compound catalysts 21. The one-dimensional metal compound catalysts 21 are wound around the outer surface of the inner core, which can not only reduce the decomposition potential of the lithium-rich material 10, but also provide good protection and support for the inner core.

[0051] Generally, during the battery charging or discharging process, when the lithium-rich material 10 in the core is lithiated or delithiated, the atomic lattice of the lithium-rich material 10 is easily deformed and expanded, which leads to the powdering and shedding of the battery pole piece, reducing the electrochemical performance and service life of the lithium-ion battery. At the same time, during the assembly, storage and transportation of lithium-ion batteries, the pole piece is easily squeezed, and the squeezing of the pole piece may cause the structure of the lithium-rich material 10 on the pole piece to be destroyed, thereby affecting the performance of the battery.

[0052] In the embodiment of the present application, the one-dimensional metal compound catalyst 21 is wound and distributed on the outer surface of the inner core. On the one hand, it can provide good protection and support for the inner core. For example, the winding of the one-dimensional metal compound catalyst 21 can play a certain buffering role on the inner core, alleviate the volume expansion problem of the inner core, and prevent the generation of internal cracks. And the winding layer formed by the one-dimensional metal compound catalyst 21 can also play an insulating role, which can prevent the external water vapor from corroding the lithium-rich material 10 and can isolate the lithium-rich material 10 from the electrolyte, reduce the occurrence of side reactions on the surface of the inner core, and improve the interface stability of the lithium supplement additive 1.

[0053] On the other hand, by filling the conductive material 30 into the gaps between the one-dimensional metal compound catalysts 21, the contact area between the conductive material 30 and the metal compound catalyst 21 is increased, and the conductivity of the metal compound catalyst 21 is improved, thereby effectively enhancing the ability of the metal compound catalyst 21 to catalyze the decomposition of the lithium-rich material 10. In addition, the conductive material 30 is bound to the gaps between the one-dimensional metal compound catalysts 21, which can prevent the conductive material 30 from falling off during the charge and discharge process, so as to ensure that the conductive material 30 can normally play the role of improving the conductivity of the lithium-rich material 10. At the same time, since the conductive material 30 is filled in the gaps between the one-dimensional metal compound catalysts 21, the compaction density of the one-dimensional metal compound catalyst 21 is increased, so that the lithium supplement additive 1 has a higher volume energy density.

[0054] In one embodiment, the conductive material 30 is coated on the outer surface of the inner core, and the composite catalytic material 20 is wrapped around the outer surface of the conductive material 30. The conductive material 30 and the composite catalytic material 20 are sequentially distributed on the outer surface of the lithium-rich material 10, and the contact area between the lithium-rich material 10 and the conductive material 30 is large, which is beneficial to improving the conductivity of the lithium-rich material 10. In addition, the contact area between the composite catalytic material 20 and the conductive material 30 is large, which can improve the conductivity of the composite catalytic material 20, thereby enhancing the catalytic effect of the composite catalytic material 20.

[0055] In one embodiment, the composite catalytic material 20 is wrapped around the outer surface of the inner core, and the conductive material 30 is coated on the outer surface of the composite catalytic material 20. The composite catalytic material 20 and the conductive material 30 are sequentially distributed on the outer surface of the lithium-rich material 10. The composite catalytic material 20 has a large contact area with the lithium-rich material 10, which is beneficial to reducing the delithiation potential of the lithium-rich material 10. At the same time, the composite catalytic material 20 has a large contact area with the conductive material 30, which can improve the conductivity of the composite catalytic material 20, thereby effectively enhancing the ability of the composite catalytic material 20 to catalyze the decomposition of the lithium-rich material 10.

[0056] In one embodiment, the conductive material 30 is in the form of particles or sheets, part of the conductive material 30 is filled into the gaps between the one-dimensional metal compound catalysts 21, and the other part of the conductive material 30 is dispersed in the core. The contact area between the conductive material 30 and the lithium-rich material 10 is increased, which is more conducive to effectively improving the conductivity of the lithium-rich material 10.

[0057] In one embodiment, the lithium-rich material 10 includes a pore structure, a portion of the one-dimensional metal compound catalyst 21 is disposed in the pore structure of the lithium-rich material 10, and another portion of the one-dimensional metal compound catalyst 21 is wound and distributed on the outer surface of the lithium-rich material 10. In the embodiment of the present application, the one-dimensional metal compound catalyst 21 is disposed in the pore structure of the lithium-rich material 10, which increases the contact area between the lithium-rich material 10 and the one-dimensional metal compound catalyst 21, and is more conducive to reducing the decomposition potential of the lithium-rich material 10.

[0058] See also Figure 2 and Figure 3 In one embodiment, the lithium supplement additive 1 includes a conductive fiber 31, the conductive fiber 31 is wrapped around the outer surface of the inner core, and the composite catalytic material 20 is wrapped around the outer surface of the conductive fiber 31. Among them, the outer surface of the lithium-rich material 10 is sequentially distributed with the conductive fiber 31 and the composite catalytic material 20. In the embodiment of the present application, on the one hand, the contact area between the lithium-rich material 10 and the conductive fiber 31 is large, which is beneficial to improve the conductivity of the lithium-rich material 10. On the other hand, the contact area between the composite catalytic material 20 and the conductive fiber 31 is large, which can improve the conductivity of the composite catalytic material 20, thereby enhancing the catalytic effect of the composite catalytic material 20. On the other hand, by providing the conductive fiber 31 and wrapping the conductive fiber 31 around the outer surface of the inner core, the conductive fiber 31 can play a good protective and supporting role for the inner core, alleviate the volume expansion problem of the inner core, prevent the generation of internal cracks, and improve the stability of the lithium supplement additive 1.

[0059] In one embodiment, the composite catalytic material 20 is coated on the outer surface of the inner core, and the conductive fiber 31 is wound and coated on the outer surface of the composite catalytic material 20. The composite catalytic material 20 and the conductive material 30 are sequentially distributed on the outer surface of the lithium-rich material 10. The composite catalytic material 20 has a large contact area with the lithium-rich material 10, which is beneficial to reducing the delithiation potential of the lithium-rich material 10. At the same time, the composite catalytic material 20 has a large contact area with the conductive material 30, which can improve the conductivity of the composite catalytic material 20, thereby effectively enhancing the ability of the composite catalytic material 20 to catalyze the decomposition of the lithium-rich material 10.

[0060] In one embodiment, a plurality of gaps are formed between the conductive fibers 31, and at least part of the composite catalytic material 20 is in granular or sheet form, and the granular or sheet-like composite catalytic material 20 is filled into the gaps between the conductive fibers 31. The conductive fibers 31 are wound and distributed on the outer surface of the inner core, which can not only improve the conductivity of the inner core, but also provide good protection and support for the inner core.

[0061] In the embodiment of the present application, by providing the conductive fiber 31 and winding the conductive fiber 31 to the outer surface of the inner core, the conductive fiber 31 can provide good protection and support for the inner core. On the one hand, the winding of the conductive fiber 31 can also provide a certain buffering effect on the inner core, alleviate the volume expansion problem of the inner core, and prevent the generation of internal cracks. On the other hand, the winding layer formed by the conductive fiber 31 can also play an insulating role, which can prevent the external water vapor from corroding the lithium-rich material 10 and can isolate the lithium-rich material 10 from the electrolyte, reduce the occurrence of side reactions on the inner core surface, and improve the interface stability of the lithium-supplementing additive 1.

[0062] In the embodiment of the present application, by filling at least part of the composite catalytic material 20 into the gaps between the conductive fibers 31, on the one hand, the contact area between the composite catalytic material 20 and the conductive fibers 31 is increased, and the conductivity of the composite catalytic material 20 is improved, thereby effectively enhancing the ability of the composite catalytic material 20 to catalyze the decomposition of the lithium-rich material 10. On the other hand, the composite catalytic material 20 is bounded in the gaps of the conductive fibers 31, which can prevent the composite catalytic material 20 from falling off during the charging and discharging process, so as to ensure that the composite catalytic material 20 can normally play the role of catalyzing the decomposition of the lithium-rich material 10, so that the lithium-rich material 10 can be fully delithiated at a lower potential, thereby improving the specific capacity of the lithium-rich material 10. On the other hand, since the composite catalytic material 20 is filled in the gaps of the conductive fibers 31, the compaction density of the conductive fibers 31 is increased, so that the lithium supplement additive 1 has a higher volume energy density.

[0063] In one embodiment, the composite catalytic material 20 is in the form of particles or sheets, part of the composite catalytic material 20 is filled into the gaps between the conductive fibers 31, and the other part of the composite catalytic material 20 is dispersed in the core. The contact area between the composite catalytic material 20 and the lithium-rich material 10 is increased, which is more conducive to reducing the decomposition potential of the lithium-rich material 10.

[0064] In one embodiment, the lithium-rich material 10 includes a pore structure, a portion of the conductive fibers 31 are inserted into the pore structure of the lithium-rich material 10, and another portion of the conductive fibers 31 are wound and distributed on the outer surface of the lithium-rich material 10. In the embodiment of the present application, the conductive fibers 31 are placed in the pore structure of the lithium-rich material 10, which increases the contact area between the lithium-rich material 10 and the conductive fibers 31, and effectively improves the conductivity of the lithium-rich material 10.

[0065] See also Figure 2In one embodiment, the lithium supplement additive 1 includes a conductive fiber 31, and the conductive fiber 31 is wound around the periphery of the one-dimensional structure of the metal compound catalyst 21. Among them, the outer surface of the inner core is sequentially distributed with the one-dimensional structure of the metal compound catalyst 21 and the conductive fiber 31. In the embodiment of the present application, the one-dimensional structure of the metal compound catalyst 21 has a large contact area with the lithium-rich material 10, which is beneficial to reduce the delithiation potential of the lithium-rich material 10. At the same time, the one-dimensional structure of the metal compound catalyst 21 has a large contact area with the conductive material 30, which can improve the conductivity of the composite catalytic material 20, thereby effectively enhancing the ability of the composite catalytic material 20 to catalyze the decomposition of the lithium-rich material 10. In addition, the one-dimensional structure of the metal compound catalyst 21 and the conductive fiber 31 are both wrapped around the inner core, which can better protect and support the inner core and improve the structural stability of the lithium-rich material 10.

[0066] In one embodiment, the conductive fibers 31 and the one-dimensional metal compound catalyst 21 are interlaced and distributed on the outer surface of the inner core. The conductive fibers 31 and the one-dimensional metal compound catalyst 21 are interlaced and distributed to form a cage structure, and the lithium-rich material 10 is contained inside the cage structure.

[0067] In the embodiment of the present application, the cage structure formed by the staggered distribution of the two one-dimensional materials has a higher structural strength. On the one hand, it can better protect and support the inner core, thereby improving the structural stability of the lithium-rich material 10. On the other hand, the conductive fiber 31 and the one-dimensional metal compound catalyst 21 are staggered and entangled, which improves the bonding tightness between the conductive fiber 31 and the one-dimensional metal compound catalyst 21, which is not only beneficial to improving the conductivity of the metal compound catalyst 21, but also can reduce the loss of the conductive fiber 31 and the metal compound catalyst 21.

[0068] In one embodiment, the inner core is a secondary particle, and the secondary particle is composed of a plurality of primary particles, and part of the composite catalytic material 20 is wound and filled in the gaps between the primary particles or coated on the outer surface of the primary particles. Part of the composite catalytic material 20 is distributed on the outer surface of the secondary particles, and part of the composite catalytic material 20 is also filled in the gaps between the primary particles or coated on the outer surface of the primary particles. That is, the interior of the lithium supplement additive 1 also has a composite catalytic material 20.

[0069] In the embodiment of the present application, the composite catalytic material 20 is coated on the outer surface of the secondary particles and on the outer surface of the primary particles or filled between the primary particles, which improves the structural stability of the primary particles and the tightness of the connection between the primary particles, and makes the overall structure of the secondary particles tighter. The lithium-rich material 10 is tightly combined with the composite catalytic material 20, which effectively reduces the delithiation potential of the lithium-rich material 10 and effectively enhances the conductivity of the lithium-rich material 10.

[0070] In one embodiment, the metal compound catalyst 21 includes one or more of transition metal carbides, transition metal nitrides, transition metal borides, and transition metal sulfides. Transition metal carbides, transition metal nitrides, transition metal borides, and transition metal sulfides have good catalytic ability and help reduce the decomposition potential of the lithium-rich material 10.

[0071] In one embodiment, the metal catalyst 22 includes one or more of nickel, iron, cobalt, manganese, copper, zinc, titanium, and chromium. Nickel, iron, cobalt, manganese, copper, zinc, titanium, and chromium have certain catalytic abilities and good electrical conductivity. Nickel, iron, cobalt, manganese, copper, zinc, titanium, and chromium are loaded on the metal compound catalyst 21 to improve the electrical conductivity of the metal compound catalyst 21, thereby enhancing the catalytic ability of the metal compound catalyst 21.

[0072] In one embodiment, the outer surface of the one-dimensional metal compound catalyst 21 is also coated with a carbon material. The carbon material can improve the conductivity of the catalyst fiber, so that the catalyst fiber can play a better catalytic effect.

[0073] In one embodiment, the mass ratio of the lithium-rich material 10, the metal compound catalyst 21 and the metal catalyst 22 is 100:(8-36):(4-22). Optionally, the mass ratio of the lithium-rich material 10, the metal compound catalyst 21 and the metal catalyst 22 is 100:(14-22):(4-8). Among them, the relative contents of the lithium-rich material 10, the metal compound catalyst 21 and the metal catalyst 22 affect the performance of the lithium-replenishing additive 1. If the content of the lithium-rich material 10 is too small, the lithium-replenishing effect of the lithium-rich material 10 is poor, and the contents of the metal compound catalyst 21 and the metal catalyst 22 are large, which will affect the energy density of the battery and thus reduce the battery capacity. If the content of the lithium-rich material 10 is too large and the contents of the metal compound catalyst 21 and the metal catalyst 22 are too small, the role of the composite catalytic material 20 and the conductive material 30 in reducing the delithiation potential of the lithium-replenishing additive 1 is not obvious.

[0074] In the embodiment of the present application, by adjusting the mass ratio of the lithium-rich material 10, the metal compound catalyst 21 and the metal catalyst 22 to 100:(8-36):(4-22), the lithium-rich material 10 can provide sufficient lithium ions to offset the irreversible lithium loss caused by the formation of the SEI film, and while reducing the delithiation potential of the lithium replenishing additive 1, the metal compound catalyst 21 and the metal catalyst 22 will not increase the mass of the lithium replenishing additive 1 too much, thereby avoiding the excessive mass of the composite catalytic material 20 and the conductive material 30, which affects the energy density of the battery and thus reduces the battery capacity.

[0075] In one embodiment, the length of the one-dimensional metal compound catalyst 21 is 3 μm to 20 μm. The length of the one-dimensional metal compound catalyst 21 affects the performance of the lithium supplement additive 1. The length range of the one-dimensional metal compound catalyst 21 in the embodiment of the present application can ensure that the one-dimensional metal compound catalyst 21 is smoothly wrapped around the outer surface of the lithium-rich material 10, reduce the lithium decomposition potential of the lithium-rich material 10, and reduce the influence of the one-dimensional metal compound catalyst 21 on the extraction and embedding of lithium ions, thereby improving the transmission rate of lithium ions, so that the lithium supplement additive 1 in the present application has higher structural stability and better electrochemical performance.

[0076] In one embodiment, the diameter of the one-dimensional metal compound catalyst 21 is 200nm to 800nm. The diameter of the one-dimensional metal compound catalyst 21 affects the performance of the lithium supplement additive 1. The diameter range of the one-dimensional metal compound catalyst 21 in the embodiment of the present application makes the one-dimensional metal compound catalyst 21 have greater strength and toughness, not only not easy to break and agglomerate, but also can better protect, buffer and reduce the decomposition potential of lithium-rich material 10.

[0077] In one embodiment, the lithium-rich material 10 includes a binary lithium supplement and / or a ternary lithium supplement. The general chemical formula of the binary lithium supplement is Li x1 M y1 , wherein M is at least one element selected from S, P, N, F, B, O, Se, Te, Br, and I, 1≤x1≤5, 0≤y1. Binary lithium supplements include but are not limited to Li 3 N.Li 2 S, LiF, Li 3 P.Li 2 Se, Li 2 At least one of O. In the present application, the binary lithium supplement agent is matched with the composite catalytic material 20 and the conductive material 30, so that the lithium supplement additive 1 has a more excellent lithium supplement effect.

[0078] Optionally, the chemical formula of the ternary lithium supplement is Li a M b O c , wherein M is at least one element selected from Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1≤a≤8, 0<b, 0<c<7. In a specific embodiment, the ternary lithium supplement may be Li 5 FeO 4 , Li 6 MnO 4 , Li 6 CoO4 , Li 6 ZnO 4 , Li 2 NiO 2 , Li 2 CuO 2 , Li 2 CoO 2 , Li 2 MnO 2 , Li 2 Ni 0.5 Mn 1.5 O 4 , Li 2 Ni d Cu (1-d) O 2 (0<d<1) etc. The lithium-rich material 10 can also be Li 2 C 2 O 4 , Li 2 CO 3 wait.

[0079] In another embodiment, the lithium-rich material 10 may also be a positive electrode material. The chemical formula of the positive electrode material is Li 1+x2 A y2 O z , wherein 0<x2≤1.2, 1≤y2<3, z>0, and A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg.

[0080] The present application provides a method for preparing a lithium supplement additive 1, and the method for preparing the lithium supplement additive 1 comprises:

[0081] The composite catalytic material 20 is mixed with the lithium-rich material 10, and heated or freeze-dried to obtain the lithium supplement additive 1.

[0082] When the lithium-rich material 10 is resistant to high temperatures, the composite material can be combined with the outer surface of the lithium-rich material 10 by heating. When the lithium-rich material 10 is easily decomposed at high temperatures, the composite material can be combined with the outer surface of the lithium-rich material 10 by freeze drying.

[0083] In one embodiment, when the lithium supplement additive 1 further includes a conductive material 30, the preparation method of the lithium supplement additive 1 includes:

[0084] Step S1, mixing the composite catalytic material 20 and the conductive material 30, and heating to obtain a composite material;

[0085] Step S2, mixing the composite material with the lithium-rich material 10, and heating or freeze-drying to obtain the lithium supplement additive 1.

[0086] Among them, step S1 is used to convert the composite catalytic material 20 and the conductive material 30 into a composite material. In step S2, the composite material is bonded to the outer surface of the lithium-rich material 10, thereby obtaining the lithium supplement additive 1. When the lithium-rich material 10 is resistant to high temperatures, the composite material can be bonded to the outer surface of the lithium-rich material 10 by heating. When the lithium-rich material 10 is easily decomposed at high temperatures, the composite material can be bonded to the outer surface of the lithium-rich material 10 by freeze-drying.

[0087] In one embodiment, the composite catalytic material 20 is a one-dimensional structure, the conductive material 30 is a conductive fiber 31, and the composite material is a composite of the one-dimensional composite catalytic material 20 and the conductive fiber 31. The one-dimensional composite catalytic material 20 and the conductive fiber 31 are sintered or freeze-dried together with the lithium-rich material 10, and the one-dimensional composite catalytic material 20 and the conductive fiber 31 are coated on the surface of the lithium-rich material 10 by intermolecular forces. The one-dimensional composite catalytic material 20 and the conductive fiber 31 can provide sufficient catalytic active sites for the lithium-rich material 10, and the two form a whole, thereby improving the conductivity and catalytic performance of the composite catalytic material 20, and playing a role in significantly reducing the delithiation potential of the lithium-rich material 10.

[0088] Exemplarily, the method for preparing the composite material comprises: 2 (MoO 4 ) 3 Nanowires and carbon fibers were dissolved in a mixed solvent of ethanol and deionized water, and dopamine hydrochloride was dissolved in deionized water. After the two solutions were completely dissolved, the two solutions were mixed, and ammonia was added dropwise to adjust the pH to a weak alkaline state. The reaction was stirred at room temperature for 20 hours to obtain Fe coated with polydopamine. 2 (MoO 4 ) 3 and carbon fiber. Then the Fe 2 (MoO 4 ) 3 The Mo with one-dimensional nanowire structure was obtained by annealing carbon fiber at high temperature in an inert gas atmosphere. 2 C, Fe, C composite nanomaterials.

[0089] Among them, through Fe 2 (MoO 4 ) 3 Adding excess one-dimensional carbon materials to nanowires can not only ensure that Fe 2 (MoO 4 ) 3The iron oxide and molybdenum oxide formed by decomposition can completely form iron and molybdenum carbide. There is no oxide in the composite material, which can improve the overall conductivity of the composite catalytic material 20 and the catalytic active sites between the composite catalytic material 20 and the lithium-rich material 10, thereby improving the conductivity and catalytic performance of the composite catalytic material 20, and playing a role in significantly reducing the delithiation potential of the lithium-rich material 10.

[0090] In one embodiment, Fe 2 (MoO 4 ) 3 The preparation method of the nanowires includes: dissolving ferric nitrate nonahydrate and nitric acid in deionized water, dissolving ammonium molybdate tetrahydrate in deionized water, and then mixing the two to control the molar mass ratio of Fe to Mo to be 2:3; transferring the mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction at 130°C to 190°C for 16 to 30 hours, and washing the obtained precursor product; calcining the obtained precursor powder in air at a calcination temperature of 550 to 650°C for 10 to 12 hours to obtain Fe 2 (MoO 4 ) 3 Nanowires.

[0091] The present application provides a positive electrode plate, which includes the lithium supplement additive 1 as described above, or includes the lithium supplement additive 1 prepared by the preparation method of the lithium supplement additive 1 as described above.

[0092] The present application provides a secondary battery, which includes a negative electrode plate, a separator and the positive electrode plate as described above.

[0093] In order to illustrate the beneficial effects of the method of the present application, the present application also provides the following examples and comparative examples:

[0094] Example 1

[0095] Embodiment 1 provides a lithium supplement additive, which includes lithium oxalate, one-dimensional molybdenum carbide, granular iron and carbon fiber, wherein the iron is embedded in the one-dimensional molybdenum carbide, the one-dimensional carbon fiber is wound around the one-dimensional molybdenum carbide, and then wound around the outer surface of the lithium oxalate. The mass ratio of lithium oxalate, molybdenum carbide and iron is 100:32:8.

[0096] The preparation method of the lithium supplement additive comprises:

[0097] Step 1: Fe 2 (MoO 4 ) 3Nanowires and carbon fibers were dissolved in a mixed solvent of ethanol and deionized water, and dopamine hydrochloride was dissolved in deionized water. After the two solutions were completely dissolved, they were mixed, and ammonia was added dropwise to adjust the pH to a weak alkaline state. The reaction was stirred at room temperature for 20 hours to obtain Fe coated with polydopamine. 2 (MoO 4 ) 3 and carbon fiber.

[0098] Step 2: Fe coated with polydopamine 2 (MoO 4 ) 3 The catalyst fiber and the carbon fiber are annealed at high temperature in an inert gas to obtain a composite nanomaterial of the catalyst fiber and the carbon fiber having a one-dimensional nanowire structure, wherein the catalyst fiber includes molybdenum carbide and iron.

[0099] Step 3: doping the obtained composite nanomaterial with the lithium-rich material in an appropriate proportion, and then calcining them at a high temperature of 450-600° C. for 4-8 hours under an inert atmosphere to finally obtain a lithium supplement additive.

[0100] Example 2

[0101] Example 2 provides a lithium supplement additive, which is different from Example 1 in that in Example 2, molybdenum carbide and iron are both in granular form, and the iron is loaded on molybdenum carbide.

[0102] Example 3

[0103] Example 3 provides a lithium supplement additive, which is different from Example 1 in that, in Example 3, iron element is filled in the gaps between the one-dimensional molybdenum carbides.

[0104] Example 4

[0105] Example 4 provides a lithium supplement additive, which is different from Example 1 in that in Example 4, the carbon fibers are carbon particles, and the carbon particles are filled in the gaps of the one-dimensional structure of molybdenum carbide.

[0106] Example 5

[0107] Example 5 provides a lithium supplement additive, which is different from Example 1 in that in Example 5, the carbon fibers are carbon particles, and the one-dimensional molybdenum carbide and carbon particles are sequentially coated on the outer surface of lithium oxalate.

[0108] Example 6

[0109] Example 6 provides a lithium supplement additive, which is different from Example 1 in that, in Example 6, carbon fiber and one-dimensional molybdenum carbide are sequentially wound around the outer surface of lithium oxalate.

[0110] Example 7

[0111] Example 7 provides a lithium supplement additive, which is different from Example 1 in that the mass ratio of lithium oxalate, molybdenum carbide and iron is 100:14:8.

[0112] Example 8

[0113] Example 8 provides a lithium supplement additive, which is different from Example 1 in that the composite catalytic material is molybdenum nitride and manganese, wherein the manganese is embedded in the one-dimensional structure of molybdenum nitride.

[0114] Comparative Example 1

[0115] Comparative Example 1 provides a lithium supplement additive, which is different from Example 1 in that molybdenum carbide is not included in Comparative Example 1.

[0116] Comparative Example 2

[0117] Comparative Example 2 provides a lithium supplement additive, which is different from Example 1 in that, in Comparative Example 2, no iron element is included.

[0118] The lithium supplement additives provided in the above examples and comparative examples are respectively assembled into positive electrode sheets and lithium ion batteries according to the following methods:

[0119] Positive electrode: The lithium supplement additive, polyvinylidene fluoride and SP-Li are mixed in a mass ratio of 80:8:12 by ball milling to obtain a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;

[0120] Negative electrode: Graphite, carboxymethyl cellulose (CMC), SBR and SP were mixed in a mass ratio of 95.8:1.2:2:1, and the mixture was ball-milled and stirred to obtain a negative electrode slurry. The negative electrode slurry was coated on the surface of copper foil, and vacuum dried at 110°C overnight to obtain a negative electrode sheet.

[0121] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF was added 6 , forming an electrolyte, LiPF 6 The concentration is 1 mol / L. In addition, some electrolyte additives are added, and the electrolyte can withstand a high voltage of 4.9V.

[0122] Diaphragm: Polypropylene microporous separator;

[0123] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of graphite negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0124] Related performance tests

[0125] Test method for electronic conductivity:

[0126] The resistivity of the positive electrode lithium supplement material in each embodiment and comparative example was calculated and tested by a four-probe method, and the electronic conductivity was obtained by taking the inverse of the resistivity.

[0127] Electrochemical performance test:

[0128] The electrochemical performance of each lithium ion battery assembled in the above lithium ion battery embodiment was tested as shown in Table 1, and the test conditions were as follows:

[0129] Constant current and constant voltage charging, the first cycle charge and discharge voltage is 2.0-4.9V, the current is 0.1C, and the cut-off current is 0.01C.

[0130] The test results are shown in Table 1 below:

[0131] Table 1 Performance test results

[0132]

[0133]

[0134] From the test results of Example 1 and Comparative Examples 1 and 2 in Table 1, it can be seen that for Li 2 C 2 O 4 Li 2 O. Li 2 O 2 、LiOH、Li 4 SiO 4 , Li 3 PO 4 , Li 2 CO 3 For lithium-rich compounds with high voltage platforms such as lithium ions, the addition of nano-scale metal compound catalysts and metal catalysts can lower their voltage platforms and improve their electrical conductivity and first charge capacity.

[0135] Comparing the performance of lithium ion batteries in Examples 1 to 8 and Comparative Examples 1 and 2, it can be seen that the various morphological particle sizes and spatial position relationships of the composite catalytic materials formed by the added metal compound catalyst and the metal element catalyst are all suitable for the composite positive electrode lithium supplement material system, and also have a significant effect on its charging voltage platform, conductivity and first charge capacity. When only the metal element catalyst is added without the metal compound catalyst, the charging voltage platform of the composite positive electrode lithium supplement material in Comparative Example 1 is higher, greater than 4.7V, and the first charge capacity is low, and the conductivity is low. When only the metal compound catalyst is added without the metal element catalyst, the charging voltage platform of the composite positive electrode lithium supplement material in Comparative Example 2 is higher, greater than 4.6V, and the first charge capacity is low, and the conductivity is low, but compared with Comparative Example 1, the voltage platform has decreased and the conductivity has increased, but compared with Examples 1 to 8, only the metal compound catalyst or the metal element catalyst is added, and the effect is worse than the composite catalytic material in this application, that is, the catalyst formed by the metal compound catalyst and the metal element catalyst.

[0136] Compared with Example 1, Example 2, Example 3 and Example 4, it can be seen that the conductive carbon material and the metal element are uniformly loaded on the surface of the metal compound, and the corresponding charging platform is low, the conductivity is high and the first charge capacity is high. Whether it is a conductive carbon material or a metal element, filling and distributing it in the gaps of the metal compound nanowires will increase the charging platform, especially when the molybdenum carbide and the iron element are both granular, the binding force between the two is weaker than that in Example 1, and the two are easy to agglomerate and have a small contact area. Compared with Example 1, the charging voltage platform in Example 2 is significantly improved. In addition, when the conductive carbon material exists in the gaps of the metal compound nanowires in the form of a 0-dimensional sphere, the catalytic effect will be significantly reduced. This is because the nanoscale particles of the carbon material are more likely to agglomerate together, reducing the overall conductivity.

[0137] Comparing Example 1, Example 5 and Example 6, it can be seen that the various positional relationships between the one-dimensional metal compound catalyst and the conductive carbon material are all suitable for incorporating the catalyst into the lithium-rich material system, but the degree of contact between the two and the degree of contact with the lithium-rich material will significantly affect the catalytic effect of the catalyst. This is because the catalytic performance of the metal compound catalyst on the lithium-rich material is affected by the conductivity, and the conductive carbon material is first loaded on the metal compound catalyst, and the two are then wound together and loaded on the surface of the lithium-rich material, which is more conducive to the close contact between the three. In Examples 5 and 6, the carbon fiber is only in contact with the inner surface or outer surface of the molybdenum carbide winding layer, and the contact area is small, so the charging voltage platform in Examples 5 and 6 is higher than that in Example 1.

[0138] Comparing Example 1, Example 7, Example 8 with Comparative Example 1 and Comparative Example 2, it can be seen that within a certain range, the ratio and type of the metal compound catalyst and the metal element are suitable for the positive electrode lithium-rich material system, but the ratio and type of the two will have a significant effect on the performance of the system. Comparing the performance of the lithium-ion batteries in Example 1, Example 7 and Example 8, it can be seen that with the increase of the content of the metal compound, the charging platform of the corresponding composite positive electrode lithium-rich material is significantly reduced, and the first charge capacity will also increase significantly. Compared with the composite catalytic material formed by the composite of molybdenum carbide and iron element in Comparative Example 1, the catalytic effect of the composite catalytic material formed by the composite of molybdenum nitride and manganese element is poor. Compared with Comparative Example 1 and Comparative Example 2, it can be seen that the synergy of the metal compound catalyst and the metal element catalyst will have a significant effect on the potential of the positive electrode lithium-rich material. Only one of them exists, and the catalytic effect produced is poor.

[0139] The above results show that the composite positive electrode lithium replenishing material of the embodiment of the present application can effectively replenish the lithium ions consumed by the formation of SEI film, significantly reduce the charging voltage platform of the lithium-ion battery, and significantly improve the conductivity and first-charge specific capacity of the lithium-rich material, thereby improving the electrochemical performance and expanding the voltage range in which the lithium-rich material can be used.

[0140] The lithium supplement additive and its preparation method, positive electrode plate and secondary battery provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and embodiments of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific embodiments and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A lithium supplement additive, characterized in that: The lithium supplement additive comprises: A lithium-rich material, the lithium-rich material forms a core, the lithium-rich material comprises a lithium-rich compound with a high delithiation voltage; and A composite catalytic material, the composite catalytic material comprising a metal compound catalyst and a metal catalyst supported on the metal compound catalyst, the composite catalytic material being coated on the outer layer of the inner core; The metal compound catalyst includes one or more of transition metal carbides, transition metal nitrides, transition metal borides, and transition metal sulfides; and / or The metal catalyst includes one or more of nickel, iron, cobalt, manganese, copper, zinc, titanium and chromium; and / or The mass ratio of the lithium-rich material, the metal compound catalyst and the metal catalyst is 100:(8-36):(4-22).

2. The lithium supplement additive according to claim 1, characterized in that: The metal compound catalyst is a one-dimensional structure; and / or the metal catalyst is a metal particle or a metal atom cluster.

3. The lithium supplement additive according to claim 2, characterized in that: The metal catalyst is at least partially embedded in the one-dimensional structured metal compound catalyst.

4. The lithium supplement additive according to claim 2, characterized in that: The lithium supplement additive further includes a conductive material, the composite catalytic material is wound and distributed on the outer surface of the inner core, and the conductive material is filled in the gaps between the metal compound catalysts of the one-dimensional structure; or The conductive material is coated on the outer surface of the inner core, and the composite catalytic material is wrapped around the outer surface of the conductive material; or The composite catalytic material is wrapped around the outer surface of the inner core, and the conductive material is wrapped around the outer surface of the composite catalytic material.

5. The lithium supplement additive according to claim 2, characterized in that: The lithium supplement additive further includes conductive fibers, the composite catalytic material is coated on the outer surface of the inner core, and the conductive fibers are wound around and coated on the outer surface of the composite catalytic material; or The conductive fibers are wrapped around the outer surface of the inner core, and the composite catalytic material is wrapped around the outer surface of the conductive fibers.

6. The lithium supplement additive according to claim 2, characterized in that: The lithium supplement additive includes conductive fibers, and the conductive fibers are wound around the outer periphery of the one-dimensional structured metal compound catalyst.

7. The lithium supplement additive according to claim 2, characterized in that: The inner core is a secondary particle, the secondary particle is composed of a plurality of primary particles, and part of the composite catalytic material is filled in the gaps between the primary particles; and / or, Part of the composite catalytic material is coated on the outer surface of the primary particle.

8. The lithium supplement additive according to claim 2, characterized in that: The one-dimensional structure of the metal compound catalyst has a length range of 3 μm to 20 μm and a diameter range of 200 nm to 800 nm.

9. A method for preparing a lithium supplement additive, characterized in that: The preparation method of the lithium supplement additive is used to prepare the lithium supplement additive according to any one of claims 1 to 8, and the preparation method of the lithium supplement additive comprises: The composite catalytic material is mixed with the lithium-rich material, and heated or freeze-dried to obtain the lithium supplement additive.

10. A positive electrode sheet, characterized in that: The positive electrode plate includes the lithium supplement additive according to any one of claims 1 to 8, or includes the lithium supplement additive prepared by the preparation method of the lithium supplement additive according to claim 9.

11. A secondary battery, characterized in that: The secondary battery comprises a negative electrode sheet, a separator and the positive electrode sheet as claimed in claim 10.